2018
DOI: 10.1007/s10709-018-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

ITS2 sequence–structure phylogeny reveals diverse endophytic Pseudocercospora fungi on poplars

Abstract: For matching the new fungal nomenclature to abolish pleomorphic names for a fungus, a genus Pseudocercospora s. str. was suggested to host holomorphic Pseudocercosproa fungi. But the Pseudocercosproa fungi need extra phylogenetic loci to clarify their taxonomy and diversity for their existing and coming species. Internal transcribed spacer 2 (ITS2) secondary structures have been promising in charactering species phylogeny in plants, animals and fungi. In present study, a conserved model of ITS2 secondary struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…DNA barcodes is an e cacious molecular tool that can provide species-level resolution to distinguish various creatures differentiation, currently has been widely used in plant identi cation 23 . The ITS2 sequence has been recommended as an effective core molecular marker of the DNA barcode 24 , which can be used to verify a wider range of herbal species groups with high variability and species discrimination 25 . These advantages make ITS2 sequence becomes a prospective barcode gene target to increase the success rate of LAMP assay.…”
Section: Introductionmentioning
confidence: 99%
“…DNA barcodes is an e cacious molecular tool that can provide species-level resolution to distinguish various creatures differentiation, currently has been widely used in plant identi cation 23 . The ITS2 sequence has been recommended as an effective core molecular marker of the DNA barcode 24 , which can be used to verify a wider range of herbal species groups with high variability and species discrimination 25 . These advantages make ITS2 sequence becomes a prospective barcode gene target to increase the success rate of LAMP assay.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a substantial number of studies have demonstrated the ITS2 molecular morphometrics approach to produce significant vital phylogenetic information for delimiting the eukaryotes at different taxonomic levels, especially at genus and species ranks [3135]. ITS2, a sub-region of ITS genetic marker, lies between the 5.8S and 28S genes of tandemly repeated rRNA genes.…”
Section: Introductionmentioning
confidence: 99%